(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides an overview of human rights concerns during the coronavirus outbreak, the examples of government responses to date, global issues resulted from pandemic and recommendations to handle with pandemic situation. Supply chain and labor privacy issues were discussed and possible solutions were recommended.